Is access to tractor service a binding constraint for Nepali Terai farmers? - Takeshima, Hiroyuki; Adhikari, Rajendra Prasad; Kumar, Anjani (International Food Policy Research Institute, 2016)
Using results from the three rounds of Nepal Living Standard Surveys (conducted in 1995, 2003, and 2010), this study empirically assesses whether access to rented tractors or custom hiring services is a binding constraint on the income growth of farm households in Nepal. Because four-wheel tractors of medium horsepower are still the primary suppliers of these tractor services, access to these services can be restricted. First, we investigated the determinants of the adoption of hired tractors as well as the intensity of their use (measured by real annual expenditures on renting tractors). Results suggest that the adoption and the intensity patterns are generally consistent with the conventional theory of the demand for agricultural mechanization, indicating that the supply of these services may be relatively efficient in meeting the demand. However, adoption is still affected by the presence of tractor owners within the same village district committee, indicating that the proximity to tractor service providers may still partly determine accessibility. This second point was more formally tested using matching estimators within the Terai region of Nepal. It was found that, on average, the supply of tractor services might have evolved to a relatively efficient level in the Terai so that those who benefited from renting in tractors generally had access to such services. However, for at least certain segments of farm households in the Terai, insufficient access to tractor services was still a binding constraint on the growth of farm household incomes. The policy implications of these findings are briefly discussed in the last section.